Comparison of indirect immunofluorescence and ELISA for the diagnosis of Neospora caninum in alpacas - Serrano-Martínez, Enrique (2023)
The aim of this study was to compare the techniques of indirect immunofluorescence (IFAT) and Enzimo inmunoensayo (ELISA) techniques for the diagnosis of Neospora caninum Dubey, Carpenter, Speer, Topper & Uggla, 1988 in alpacas from the highlands of Peru. Sensitivity, specificity, positive predictive value, negative predictive value and concordance of IFAT were evaluated using a commercial competitive ELISA kit (cELISA - VMRD) as a reference. 1540 sera samples were collected from alpacas naturally exposed to N. caninum. The results showed good sensitivity (92.95%), high specificity (99.75%), positive predictive value of 92.90% and a negative predictive value of 99.04%. The concordance between both diagnostic techniques (IFAT and ELISA) turned out to be almost perfect (k = 0.98). It is concluded that the IFAT test has a high efficiency for the diagnosis of N. caninum in alpacas.